Building-up urban scenarios: assessing institutional feasibility and political viability of strategic trajectories - Karol, Jorge Leonardo (2010)
The paper discusses a simple methodological tool for supporting the participatory elaboration of future urban scenarios through successive approximations. It systematizes one possible way to build answers to a set of critical questions when attempting to compose strategic urban programs. To this end, we focused on devising a simple sequence of understandable, easy-to-apply Multi Criteria Evaluation instruments which - by means of ‘light’ ‘accounting’ calculation procedures - may “help (planners) to think” (Calcagno, 1972). The deliberate simplicity of this approach - an ‘intelligent’, transparent and intentional management of elements of analytical and intervention fields, funded on their exhaustive qualitative descriptions and on explicit statements of interests and purposes - prioritises the political side of decision – making. Thus, the paper also seeks to contribute to the reflection on the roles and views of social actors when defining and constructing urban public scenarios. First, we discuss the conceptual and political contents and implications of Diagnoses and Scenario- building, in which involved actors (i) elaborate causal interpretations of urban processes, (ii) specify and select strategic trajectories and (iii) compose and structure project portfolios, by (eventually) supporting them through progressive agreements and consensus. Next, we propose a methodological approach to assessing institutional feasibility and political viability of given strategic trajectories. Finally, we discuss some contextual and operational conditions of these analyses. On the technical side, this framework is originally focused on the interactions among Land Use, Mobility and Energy consumption patterns, three strong determinants of the socio-spatial structuring of territories which - both in Argentina and other Latin American countries - are seldom addressed through transversal, integrated planning approaches. Quite on the contrary, public urban management models – referred to those as well as to other relevant drivers of urban structuring - are most often characterized by remarkable jurisdictional and institutional disarticulation, high technical and thematic fragmentation, ritual emphases on bureaucratic processes rather than on factual objectives or results. Accordingly, formulation and evaluation of public urban policies usually present extremely low levels of systemic completeness. It is suggested that - in these types of highly fragmented governance environments - this approach may contribute to making experts’ and social actors’ views explicit and to enabling transversal thinking. The analysis of diverse structuring, feasibility and viability assessments may – if applied through successive approximations - help planners to reconfigure the strategic composition of public policies, whether by (i) modifying the strategy portfolio, (ii) modifying the sequence of strategies or (iii)incorporating new strategies in order to modify the balance between involved actors’ rejections and supports, while maintaining the meanings, orientations and aims of the evaluated policy.